Non-alcoholic fatty liver disease: A growing public health problem in Turkey - Eda Kaya,; Yusuf Yılmaz, (Turkish Journal of Gastroenterology, 2019)
Non-alcoholic fatty liver disease (NAFLD) is histologically classified as either non-alcoholic fatty liver or non-alcoholic steatohepatitis (NASH). NASH is the progressive subtype of NAFLD. Individuals with NASH are at significant risk of developing hepatic fibrosis, cirrhosis, hepatocellular carcinoma, and liver-related and all-cause mortality. NAFLD is closely associated with obesity, type 2 diabetes mellitus (T2DM), metabolic syndrome, and cardiovascular events. Its prevalence is estimated to be above 30% in Turkey; and recent studies confirm this estimate. According to these studies, the prevalence of NAFLD in Turkey is between 48.3% and 60.1%. Currently, Turkey can be considered a risky region in terms of NAFLD burden as it is the most obese country in Europe with an obesity prevalence of 32.1% according to the 2016 World Health Organization data. Moreover, along with the increasing prevalence of obesity and T2DM in Turkey, the burden of NAFLD is estimated to increase in the upcoming decade. Despite the growing burden, we lack well-designed systemic studies that investigate NAFLD and its marked histological severity. In this review, we present studies on the burden of NAFLD and NASH, the natural history of NAFLD, and its association with other systemic diseases conducted with Turkish populations. Cite this article as: Kaya E, Yılmaz Y. Non-alcoholic fatty liver disease: A growing public health problem in Turkey. Turk J Gastroenterol 2019; 30(10): 865-71.